2015
DOI: 10.1016/j.ejim.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Approvals of drugs with uncertain benefit–risk profiles in Europe

Abstract: In most cases there was limited evidence supporting the positive benefit-risk balance at the time of approval. Delays or discrepancies in the fulfilment of obligations allow medicinal products with unsettled benefit-risk profiles onto the market for several years. This should be taken into account when further early or step-wise licensing strategies are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 32 publications
5
82
0
6
Order By: Relevance
“…Concerning expedited‐approval programmes in the EU, it has been reported that there were delays or discrepancies in the fulfilment of the post‐market obligations in more than one third of the conditional approvals (Banzi et al , 2015). Moreover, as in the example of Midodrine in the USA (Dhruva and Redberg, 2010), it has sometimes become difficult for authorities to withdraw products of questionable efficacy from the market because of appeals made by professional organizations, health care professionals and patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning expedited‐approval programmes in the EU, it has been reported that there were delays or discrepancies in the fulfilment of the post‐market obligations in more than one third of the conditional approvals (Banzi et al , 2015). Moreover, as in the example of Midodrine in the USA (Dhruva and Redberg, 2010), it has sometimes become difficult for authorities to withdraw products of questionable efficacy from the market because of appeals made by professional organizations, health care professionals and patients.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of obligations to collect and report post‐marketing data on approved drugs have been bypassed by sponsors (Moore and Furberg, 2014). In the EU also, there have been delays or discrepancies in fulfilling post‐marketing obligations in more than one third of granted conditional approvals (Banzi et al , 2015). Objections by the US congress or patient advocacy groups have reversed withdrawal decisions previously made by the legislative authorities (Dhruva and Redberg, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…13 Conditional authorisation is used most often for drugs used in oncology and infectious diseases and for orphan-designated medicines. 13–15 Examples include ▾bedaquiline for the management of multidrug-resistant tuberculosis and pazopanib hydrochloride (Votrient) for renal cell carcinoma. 15,16 …”
Section: Regulatory Tools For Faster Approval or Pre-approval Accessmentioning
confidence: 99%
“…13–15 Examples include ▾bedaquiline for the management of multidrug-resistant tuberculosis and pazopanib hydrochloride (Votrient) for renal cell carcinoma. 15,16 …”
Section: Regulatory Tools For Faster Approval or Pre-approval Accessmentioning
confidence: 99%
“…Drei KHSG-Maßnahmen adressieren dieses Problem: Seltenheit (vgl. HAI et al 2015;Banzi, R. et al 2015;Fain, K. et al 2013). Damit steigt das Risiko von Fehlentscheidungen für Ärzte, Patienten, Versicherte und das Gesundheitssystem dauerhaft (Zentner, A., Haas, A.…”
Section: Abbildung 10: Belegungstage Und Durchschnittliches Alter (19unclassified